The clinical outcomes of pediatric inguinal hernia repairs operated by surgical residents - Shohei Yoshimura (Asian Journal of Surgery, 2020)
Summary: Background: Inguinal hernia is one of the most common surgical diseases, and surgical residents perform inguinal hernia repairs during pediatric surgery rotation. The aims of this study were to examine the clinical outcomes of pediatric inguinal herniorrhaphy performed by surgical residents and to assess the suitability for surgical training. Methods: We extracted data on elective unilateral inguinal hernia repairs performed in children between 2014 and 2018. All eligible cases were divided into surgical resident and attending surgeon groups according to the operator. We reviewed medical records retrospectively and compared some clinical indicators between the 2 groups. Results: Of 294 eligible cases, 163 were performed by 37 surgical residents and 131 were performed by 4 attending surgeons. The median operative times in the resident and attending surgeon groups were 30 and 19 min, respectively. Operative time was statistically longer in the resident group (p < 0.001). The complication and recurrence rates in the resident and attending surgeon groups were 11.0% and 11.5%, and 0% and 0.8%, respectively (p = 1.000 and p = 0.466). Conclusion: Inguinal hernia repairs could be properly performed by surgical trainees with the assistance of attending surgeons. Hernia operation might provide good opportunities for surgical residents to practice basic surgical skills.